(أساليب التشبيه وأغراضه في سورة الرحمن (دراسة تحليلية بلاغية - Muhamad Arif Mustofa; Iin Safitri (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2020)
Abstract The Arabic language has branches of its sciences such as grammar, morphology, and rhetoric. Rhetoric is divided into the many inquiries, and in general it was divided into three sections: the science of meanings, the statement, and the bade. One of the topics of science statement analogy. As for this, the Qur’an verses contain the beauty of rhetorical methods. The writer chooses Surat Al-Rahman, because it contains many methods of simile and thos who read it. With this research, he wanted to investigate the methods of simile in that surah and its purposes, because the methods of imitation have special purposes and goals to confirm the meaning contained in the verse, and their purposes differ between one verse and the other verse.